A comprehensive economic assessment of the burden of obesity in Kuwait - Mouaddh Abdulmalik Nagi; Hanan Ahmed; Mohammad Almari; Ziyad S. Almalki; Yasir Mohammed Zaroug Elradi (PLoS ONE, 2026)
Background Obesity is a complex public health issue that has risen to epidemic proportions globally. The aim of this study was to estimate the economic costs associated with obesity from governmental and societal perspectives in the State of Kuwait in 2024. Methods A disease-specific prevalence-based cost-of-illness framework was applied. Key parameters include prevalence of obesity and its related comorbidities, relative risks, healthcare resources, income rate and growth, and lost workdays for patients and relatives, all were derived from literature. The outcomes measured were total healthcare costs, societal costs, and cost per patient, all reported in 2024 Kuwaiti Dinar (KWD), United States dollar ($), and Purchasing Power Parity (PPP). Results In 2024, there were approximately 2 million morbidity cases and 961 mortality cases directly attributed to obesity in Kuwait. The economic burden of obesity was estimated at KWD 4.3 billion ($ 14 billion; PPP$ 21.6 billion) from societal perspective and KWD 3.9 billion ($12.8 billion, PPP 19.7 billion) from governmental perspective, almost 1.3 times healthcare budget. The mean annual societal cost per patient was KWD 1,737 ($5,676; PPP 8,729)—17.6% of 2024 Kuwaiti gross domestic product per capita. Furthermore, the mean direct medical cost per patient was KWD 1,586 ($5,184 or PPP 7,972); comprised 3 times the healthcare expenditure per capita. Conclusion Obesity and its comorbidities impose a far greater health and economic burden on Kuwait’s healthcare system and national productivity than previously recognized. This study calls for a paradigm shift toward early prevention, culturally tailored strategies, and comprehensive disease management. Expanding access to emerging innovative treatments and leveraging technology-driven tools are essential to support sustained weight management and reduce long-term impacts.